2020
DOI: 10.1016/j.icarus.2019.113590
|View full text |Cite
|
Sign up to set email alerts
|

Crater-ray formation through mutual collisions of hypervelocity-impact induced ejecta particles

Abstract: We investigate the patterns observed in ejecta curtain induced by hypervelocity impact (2−6 km/s) with a variety of the size and shape of target particles. We characterize the patterns by an angle, defined as the ratio of the characteristic length of the pattern obtained by Fourier transformation to the distance from the impact point. This angle is found to be almost the same as that obtained by the reanalysis of the patterns in the previous study at lower impact velocities (Kadono et al., 2015, Icarus 250, 21… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…Our simulations presented in the previous section confirm the expectation by Kadono et al (2015Kadono et al ( , 2020 that the mesh pattern in ejecta evolves in two stages: initial growth through inelastic particle collisions and subsequent geometric expansion with no particle collision. However, it is yet to be addressed when the initial growth stage is terminated and what initial conditions set the final size of the clusters constituting the pattern.…”
Section: Analytic Modelsupporting
confidence: 86%
See 4 more Smart Citations
“…Our simulations presented in the previous section confirm the expectation by Kadono et al (2015Kadono et al ( , 2020 that the mesh pattern in ejecta evolves in two stages: initial growth through inelastic particle collisions and subsequent geometric expansion with no particle collision. However, it is yet to be addressed when the initial growth stage is terminated and what initial conditions set the final size of the clusters constituting the pattern.…”
Section: Analytic Modelsupporting
confidence: 86%
“…Moreover, the snapshots at 76 and 91 μs after the impact show that the pattern simply expands with the curtain (see the red circles in the lower panels of Figure 2). Kadono et al (2020) also observed the expansion of ejecta curtain patterns in their similar experiments, but at ∼10 ms after impact. Our experimental results presented here indicate that pattern formation occurs and is completed much earlier, on a timescale comparable to the expansion timescale of the ejecta curtain.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations